Dinamika Nilai Perusahaan Perbankan: Peran Debt-To-Equity Ratio Dalam Memoderasi Pengaruh Return On Assets - Benny Cuaca; Bambang Widjanarko Susilo; Edy Susanto; Ayu Miranti Kusumaningrum; Rezky Eko Prasetyo; Wesly Tumbur ML Tobing (CV Muara Edukasi, 2026)
This study aims to examine the effect of profitability (ROA) on firm value (PBV) with capital structure (DER) as a moderating variable in Indonesian banking companies. Using panel data from 15 banking companies for the 2015-2020 period, this study reveals an anomalous phenomenon where an increase in ROA is not always linear with an increase in firm value, and vice versa. Using Partial Least Squares - Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software, the results show that DER significantly moderates the effect of ROA on firm value, but with an asymmetric effect depending on macroeconomic conditions. The novelty of this study is the proposition of the concept of